A new species of the genus Onychopterocheilus Blüthgen, 1955 from the Altai Mountains, with the re-description and new records of the closely related O. kiritshenkoi (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae) - Fateryga, Alexander V.; Buyanjargal, Batchuluun (Zootaxa, 2023)
Onychopterocheilus (Asiapterocheilus) proshchalykini Fateryga, sp. nov. is described from the Altai Republic (Russia). The new species is closely related to O. (A.) kiritshenkoi (Kostylev, 1940) but distinctly differs from it by the structure of the clypeus, the female vertex and scutellum, the male genitalia, as well as the coloration. In addition, O. proshchalykini has somewhat larger body size. Onychopterocheilus kiritshenkoi is re-described. Both species have the northernmost distribution among 13 currently recognized species of the Central Asian subgenus Asiapterocheilus. Onychopterocheilus chinensis Gusenleitner, 2005 is transferred to this subgenus from the nominotypical one. Onychopterocheilus kiritshenkoi is recorded from the Altai Republic for the first time; two new localities of this species from Mongolia are also reported. Females of O. kiritshenkoi were observed at flowers of two species of Fabaceae: Caragana bungei Ledeb. and Vicia costata Ledeb. The wasps acted as primary nectar robbers, i.e., they made holes in the calyx to access nectar with their relatively long proboscises.